Between Philology and Radical Enlightenment Hermann Samuel Reimarus (1694-1768). - Mulsow, Martin (Leiden : BRILL, 2011)
Drawing on new manuscript sources, this volume offers seven contributions on Hermann Samuel Reimarus, the most significant biblical critic in eighteenth-century Germany, as well as an eminent Enlightenment philosopher, a renowned classicist, and expert on Judaism.
Preface; From Antiquarianism to Bible Criticism? Young Reimarus Visits the Netherlands; Edifying versus Rational Hermeneutics: Hermann Samuel Reimarus' Revision of Johann Adolf Hoffmann's 'Neue Erklarung des Buchs Hiob'; The Public Discourse of Hermann Samuel Reimarus and JohannLorenz Schmidt in the Hamburgische Berichte von GelehrtenSachen in 1736; Reimarus, the Cardinal, and the Remaking of Cassius Dio's Roman History; The Philosophical Context of Hermann Samuel Reimarus' RadicalBible Criticism; Living in the Enlightenment: The Reimarus Household Accounts of 1728-1780.
Index of Names.
Description based on print version record.
Keywords: Reimarus, Hermann Samuel, -- 1694-1768.; Jesus Christ -- Historicity; Reimarus, Hermann Samuel, 1694-1768 -- Contributions in studies of the historical Jesus; Reimarus, Hermann Samuel, 1694-1768.; RELIGION / Deism; Electronic books